EVOLUTION OF THE LAMINAR BOUNDARY LAYER OVER A FLAT PLATE UNDER A FREE STREAM TURBULENCE INTENSITY OF 1.3% - Walsh, E; Brighenti, F; Mceligot, D; ASME (2008)
The evolution of the laminar boundary layer over a flat plate under a free stream turbulence intensity of 1.3% is analysed. The effect of free stream turbulence on the onset of transition is one of the important sources leading to bypass transition. Such disturbances are of great interest in engineering for the prediction of transition on turbine blades. The study concentrates on the early part of the boundary layer, starting from the leading edge, and is characterised by the presence of streamwise elongated regions of high and low streamwise velocity. It is demonstrated that the so called "Klebanoff modes" are not entirely representative of the flow structures, due to the time-averaged representations used in most studies. For the conditions of this investigation it is found that the urms and the peak disturbances remain constant in the early stages of the transition development. This region, in which the streaks strength is constant, is problematic for many theories as it is not known where on a surface to initiate a growth theory calculation, and hence the prediction of transition onset is difficult. The observation that a constant urms region exists within the boundary layer under these conditions may be the source of great difficulty in predicting transition onset under turbulence levels around l%. This region suggests that the streaks are either continuously generated and damped, or do not grow during the early stage of transition, and highlights the importance of continuous influence of the free stream turbulence along the boundary layer edge. This work concludes that the first is more likely, and furthermore the measurements are shown to agree with recent direct numerical simulations. © 2008 by ASME.